Dampak Pemulihan Mangrove Terhadap Bahan Baku, Kesempatan Kerja dan Pendapatan Keluarga Pesisir - Pambudi, Julian Hisky Tyas (JURNAL AGRIUST, 2020)
This study which was conducted in the coastal area of Rugemuk Village, Pantai Labu Subdistrict, Deli Serdang Regency aims to 1) analyze the impact of mangrove forest recovery program on mangrove cover area; 2) analyze the impact of mangrove recovery program on availability of raw materials of coastal agroindustry; 3) analyze the impact of mangrove forest recovery program on employment opportunities;Â  4) analyze the impact of mangrove recovery program on coastal household income. Data analysis method used in this research is comparative method that is Wilcoxon Match Pairs Test and Test-t. Sampling method used is simple random sampling method with the number of samples of 79 samples. The results showed that 1) There is increasing mangrove forest cover area after mangrove restoration program; 2) There is significant difference availability of raw materials of coastal agroindustry; 3) There is significant difference employment opportunities before and after mangrove restoration program; 4) There is significant difference in coastal household income before and after mangrove restoration program